Ureteral endometriosis: A rare cause of silent obstructive uropathy - (:unkn) unknown (MARMARA UNIV, FAC MEDICINE, 2016)
Endometriosis is defined as the presence of active endometrial tissue outside the uterine cavity affecting 15% of women at reproductive age. Ureteral endometriosis (UE) is a rare type of endometrial involvement affecting 0.1% - 1% of women with endometriosis. UE is quite uncommon and underdiagnosed because of the patients' nonspecific symptoms of endometriosis. However, it is important to diagnose and manage UE treatment since it can lead to renal failure due to silent obstruction of the ureter. This case report describes a woman who presented with cyclic pelvic pain and left flank pain. Imaging studies and laparoscopic findings revealed bilateral endometrioma and deep infiltrating endometriosis (DIE) findings resulting in extrinsic infiltration of the ureter and hydronephrosis.
Keywords: Endometriosis; Ureter; Hydronephrosis; Magnetic resonance imaging; Laparoscopy